Defluoridation of water with the Help of Azadirachta Indica, Fecus Recemosa and Feronia Limonia leaves as Bioadsorbents - Krishna Kumar Kashyap, Basant Kulhara, Shivanand Saket, Harsha Tiwari, Manoj Kumar Ghosh, Shweta Tamrakar, Rajendra Prasad Kushwaha (Journal of Neonatal Surgery, 2025)
Depending on the nature of the processes, the defluoridation approach used thus far has included adsorption, precipitation, electrochemical, ion exchange, and membrane approaches. However, due to their high cost, inefficiency, or failure in large-scale applications, these approaches are not frequently employed. As a result, finding an excellent low-cost and ecologically acceptable approach for removing fluoride from drinking water is critical. In this study, neem (Azadirachta indica) leaf powder, gular (Fecus recemosa) leaf powder, and kaith (Feronia limonia) leaf powder were used as low-cost bioadsorbents for fluoride removal from water. For adsorption isotherms, several models have been employed to explain experimental data. However, the Langmuir, Freundlich, and Temkin isotherm models are appropriate for this investigation. The SEM & EDX examined of groundwater sample with Azadirachta indica, Ficus recemosa, and Feronia limonia leaves powder after and before treatment.